(untitled) (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2025)
Ownership Structure is believed to be able to influence the course of the company which ultimately affects the company’s performance in achieving the company’s goals, namely maximizing the Company’s value, this is due to the control it has (Jansen and Meckling, 1976). The company’s concern for ESG (Environmental, Social, and Governance) performance is one form of corporate responsibility in a sustainable business process. The purposive sampling method was used to select samples that met the criteria from 25 Plantation companies for the 2019-2023 period, 17 companies were obtained according to the criteria, so that the number of observation data was 85 observations. The SEM-PLS method was used for the analysis of this study. The results of the analysis show that financial slack moderates the relationship between ESG performance and Financial Performance with a negative coefficient, but does not moderate the relationship between Ownership Structure and Financial Performance. Therefore, the higher the financial slack, the lower the influence of ESG performance on the company’s financial performance, and the lower the financial slack in the company, the stronger the influence of ESG performance on financial performance and for the future the company will continue to grow sustainably, and will increase the Company’s Value.